BENTUK, STRUKTUR DAN MAKNA RAGAM HIAS HOTEL SAHID KUSUMA - Eko Sri Haryanto (Dewa Ruci: Jurnal Pengkajian dan Penciptaan Seni, 2009)
Dalem Kusumayudhan is a part of the Sahid Kusuma Hotel in Surakarta, and was formerly the residence of Kanjeng Gusti Pangeran Harya Kusumayudha, son of Paku  Buwana X.   It has changed ownership several times and been renovated on a number of occasions.  The last renovation being in the middle of 2008, as part of the owner’s strategy to attract more tourists to visit and stay in the Sahid Kusuma Hotel.The aim of this research is to discover the style and structure of the ornament variations of the singep tumpangsari in the Sahid Kusuma Hotel, and also the philosophical meaning contained in these ornaments, in relation to the culture of the  surrounding community.   It is hoped that the results of this research will be beneficial  for current efforts to preserve and encourage the use of traditional Javanese ornament  variations on buildings today.   The process for collecting and analyzing data and  information uses a qualitative research method.   The descrip- tion of the style,  structure, and the meaning of the ornament variations uses Gadamer’s hermeneutic  phenomenological approach.In general, the structure of the ornament variations on the object of the research complies with the structural norms of the fine arts discipline, namely: unity, pres- sure, and balance.  It is hoped that the discovery of the meaning of these ornament variations will enable others to benefit from the philosophical values contained in the ornament variations in the Sahid Kusuma Hotel, namely: leadership, superior- ity, determination,  strength, and the essence of discovering the meaning of a per- fect life.